Proposed therapeutic landscape design at Tasik Ilham, UiTM Perlis / Nour Shazana Shahiful Hizam - Shahiful Hizam, Nour Shazana (2022)
Tasik Ilham is a recreational park in UiTM Perlis, found near the main entrance of the campus and beside Star Complex which held classrooms, labs, halls, lecturer rooms, and offices. This makes the location strategic for the campus’ community to visit, especially students during the spare time between classes or in the evening. Tasik Ilham was once an attractive park with a man-made lake in the centre. However, since the imposition of the Movement Control Order (MCO) in March 2020, every physical activity and all forms of exercise recreation open space has been restricted. The maintenance routine of Tasik Ilham has also been put to a halt due to the temporary shut-down of UiTM Perlis with all the staff to be worked from home; hence, Tasik Ilham becomes deserted and empty. Therefore, the development of landscape design with a fresh image of the park will attract the campus’ community to utilize the park and give it a new breath. The design approach in this study is a therapeutic garden which will be discussed in detail later. However, the park is to be divided into areas with different activities circulated around the park. Site inventory and analysis is done at the proposed area before a design is proposed in AutoCAD drawing. Other software used includes Android compass, PlantNet, and Google sheet. A synthetic tape and digital compass are used to take the distance between plants and to measure the canopy of plants and the size of hardscapes. The outcome of this study is a master plan of a proposed therapeutic landscape design drawn in AutoCAD software.